EFFECTS OF PERIODIC SALINITY VARIATION ON THE EXPRESSION OF SOME PHENOTYPIC TRAITS IN STRIPPED DWARF CATFISH (Mystus vittatus) - S.M. Rahman; R. T. Mathew; Y. A. Alkhamis; A. S. Alsaqufi; J. Golder; I. Noor; M. M. Rahman (Journal of Animal and Plant Sciences, 2022)
Salinity fluctuations are known to have direct or indirect influence on phenotypes and thereby, evolve the subsequent life history traits in aquatic animals especially in fish. The present study was carried out to investigate whether periodic salinity fluctuations can influence the expression of some phenotypic traits (e.g. survival, standard length, tail length, body area, and body colour) in stripped dwarf catfish (Mystus vittatus). Ninety medium sized stripped dwarf catfish were collected and reared up to three months dividing into two treatments such as control treatment (CT) and salinity treatment (ST). The CT fish were reared at 0 ppt during the experimental period, while ST fish were reared at 10 ppt in first month, 0 ppt in second month and 10 ppt again in third month. There were significant effects of salinity on survival and the overall body colour of stripped dwarf catfish during the experiment. The results showed a significant difference in the tail length between the two treatments in which the average of tail length with the ST throughout the experimental period was significantly smaller than the CT. The study also found that the ST fish were significantly less bright and highly fade in appearance compared to the CT fish. The overall results have revealed an important role of periodic salinity fluctuation on the expression of some phenotypic traits in stripped dwarf catfish and thereby, underpinned the evolution of different phenotypic traits in many animals and also their plasticity as result of environmental stress in nature.
Keywords: Catfish; salinity stress; fish phenotypes; fish colour